Psychometric properties of the OHIP-14 and prevalence and severity of oral health impacts in a rural riverine population in Amazonas State, Brazil Avaliação das propriedades psicométricas do OHIP-14 e da prevalência dos impactos da saúde bucal, em população rural ribeirinha no Amazonas, Brasil - Flávia Cohen-Carneiro; Maria Augusta Bessa Rebelo; Reinaldo Souza-Santos; Gláucia Maria Bovi Ambrosano; Alessandra Valle Salino; Danielson Guedes Pontes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The objectives of this study were: (1) test the psychometric properties of OHIP-14 in a rural population; and (2) compare the oral health impacts in two riverine communities in the Brazilian Amazon that were living at different distances from an urban center. Data were obtained from a cross-sectional study in a consecutive sample (n = 126). The validity was assessed through the association of OHIP with clinical and subjective variables, which showed a more significant association with: pain, caries, need of extraction or endodontic treatment; than with tooth loss, periodontal disease or need of prostheses. The stability and internal consistency were good (ICC = 0.97; Cronbach's α = 0.89). The prevalence of oral impacts was greater in the community far from the urban center [70.3 (59.9-80.7)] than in the community closer to it [44.3 (30.7-57.7)], and in women [66.7 (56.0-77.3)] in comparison with men [49.1 (35.3-62.7)]. The OHIP-14 adapted to rural populations in Amazonas State was valid, reproducible, and consistent. There was high prevalence of impacts, especially for riverine communities that lived far from urban centers. Os objetivos do trabalho foram: (1) testar as propriedades psicométricas do OHIP-14 em população rural e (2) comparar os impactos da saúde bucal em duas comunidades ribeirinhas amazônicas, com diferentes distâncias do centro urbano. Os dados foram obtidos de uma amostra consecutiva de pacientes (n = 126) em estudo de corte transversal. A validade do instrumento foi testada pela associação do OHIP com variáveis clínicas e subjetivas, sendo mais significativa para as variáveis: dor, cárie, necessidade de extração e de endodontia que para perda dentária, doença periodontal e necessidade de prótese. Estabilidade e consistência interna foram boas (CCI = 0,97; α Cronbach = 0,89). A prevalência de impactos foi maior na comunidade mais distante do centro urbano [70,3 (59,9-80,7)] que na mais próxima [44,3 (30,7-57,7)], e nas mulheres [66,7 (56,0-77,3)] comparadas aos homens [49,1 (35,3-62,7)]. O OHIP-14 adaptado às populações rurais da Amazônia foi válido, reproduzível e consistente. A prevalência dos impactos foi alta, especialmente para ribeirinhos que vivem distante dos centros urbanos.